2013
DOI: 10.13189/ujaf.2013.010104
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Information Systems on Revenue Collection by Local Authorities in Homa Bay County, Kenya

Abstract: This paper examined the effect of Information Systems on revenue collection of Local Authorities in Homa Bay, Kenya. Study objectives included establishing the relationship between internal control systems, Information Systems and revenue collection in Kenyan Local Authorities; determining the levels of quality service offered to the clients by Local Authorities and investigating whether Information Systems relate to effectiveness and efficiency of Revenue Collection. A structured cross-section survey was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 2 publications
0
1
0
3
Order By: Relevance
“…It was established that tax payer education and revenue collection points have strong, positive and significant effect financial performance of KRA while computerized operations and staff training have strong, negative and significant effect on financial performance of KRA. Otieno et al (2013) studied effect of information systems on revenue collection by local authorities in Homa Bay County, Kenya. A structured crosssection survey was used to collect data from 2,007 individuals, of which 165 were Local Authorities staff and 1,842 were traders in Homa Bay Municipality.…”
Section: Monitoring and Evaluation And Optimization Of Revenue Collec...mentioning
confidence: 99%
“…It was established that tax payer education and revenue collection points have strong, positive and significant effect financial performance of KRA while computerized operations and staff training have strong, negative and significant effect on financial performance of KRA. Otieno et al (2013) studied effect of information systems on revenue collection by local authorities in Homa Bay County, Kenya. A structured crosssection survey was used to collect data from 2,007 individuals, of which 165 were Local Authorities staff and 1,842 were traders in Homa Bay Municipality.…”
Section: Monitoring and Evaluation And Optimization Of Revenue Collec...mentioning
confidence: 99%
“…Pemerintah daerah seharusnya dapat meningkatkan sistem administrasi perpajakan, kualitas administrator pajak, lebih menekankan upaya intensif daripada ekstensif, dan menerapkan imbalan (reward) dan hukuman (punishment) (Sitompul, Syahnur, & Ichsan, 2014). Otieno et al (2013) menemukan adanya hubungan antara sistem informasi dan efisiensi maupun keefektifan pengumpulan pendapatan pemerintah lokal. Selain itu, ada hubungan positif antara sistem pengendalian internal dan pengumpulan pendapatan.…”
Section: Kajian Teoritisunclassified
“…Selain itu, ada hubungan positif antara sistem pengendalian internal dan pengumpulan pendapatan. Resistensi terhadap perubahan dapat menghambat implementasi sistem informasi (Otieno et al, 2013). Penelitian oleh Githinji, Mwaniki, Kirwa, dan Mutongwa (2014) menemukan bahwa sistem pemungutan pajak di Kenya relatif buruk dan belum mendapatkan perhatian memadai.…”
Section: Kajian Teoritisunclassified
See 1 more Smart Citation
“…Moreover, FinTech leads government revenue and expenditure in an efficient and transparent outcomes. Previous empirical studies found that digitalization of government budget and tax were accelerated by employing FinTech in fiscal policy (Otieno, et al, 2013;El Gohary, 2019;and Cangiano et al, 2019). FinTech delivers some benefits for fiscal policy such as support better transaction for government, business, and individual.…”
Section: Introductionmentioning
confidence: 99%